Meal intake increases circulating procoagulant microparticles in patients with type 1 and type 2 diabetes mellitus. (3rd April 2019) - Spectre, Galia; Mobarrez, Fariborz; Stålesen, Ragnhild; Östenson, Claes-Göran; Varon, David; Wallen, Håkan; Hjemdahl, Paul
Abstract: Diabetes mellitus (DM) is associated with prothrombotic alterations, and postprandial hyperglycemia is an independent risk factor for cardiovascular complications. We therefore investigated whether a standardized mixed meal alters circulating microparticles (MPs) and their procoagulant activity in DM patients. Patients with DM type 1 (T1DM, n = 11) and type 2 (T2DM; n = 9) were studied before and 90 min after a standardized meal (without premeal insulin). MPs in plasma derived from platelets (PMPs), endothelial cells (EMPs), or monocytes (MMPs) were measured by flow cytometry. MP-induced thrombin generation in plasma was assessed by a calibrated automated thrombogram. In the fasting state, MPs did not differ significantly between T1DM and T2DM. Meal intake increased the following microparticles: PMPs expressing phosphatidylserine (by 55%, on average), P-selectin (by 86%), and tissue factor (TF; by 112%); EMPs expressing E-selectin (by 96%) and MMPs expressing TF (by 164%), with no significant group differences between T1DM and T2DM. There were no increments in EMPs expressing phosphatidylserine or TF. Meal intake increased MP-induced thrombin generation similarly in T1DM and T2DM with increased endogenous thrombin potential ( p = 0.02) and peak thrombin ( p = 0.03) and shortened time to peak ( p = 0.02). Phosphatidylserine inhibition by lactadherin completely abolished MP-induced thrombin generation, while an anti-TF antibody had no effect. In conclusion, meal intake increased several types of circulating MPs in patients with diabetes mellitus. These MPs have a procoagulant potential, which is related to phosphatidylserine expression and negatively charged MP surfaces rather than to TF.